Analysis of Fish Cultivation Business in Rapid Pools in Nagari Lubuk Basung, Agam District, West Sumatra Province - Fernando, Putri Deniya; Zulkarnain, Zulkarnain; Hendrik, Hendrik (Fakultas Perikanan dan Kelautan Universitas Riau, 2024)
The research was carried out in 2023 at Jorong I Siguhung Nagari Lubuk Basung, Agam Regency, West Sumatra with the aim of knowing non-financial feasibility and analyzing the financial feasibility of fish farming in a fast-water pond system. The method used in this study was a survey method and the determination of respondents was carried out using purposive sampling. Commercial aspects include the procurement of seeds and feed, prices and marketing as well as the influence of the selling price of fish on fish farming in KAD. The social aspect can see the impact of social and environmental impacts on the surrounding community. The institutional aspect can be seen from the cultivator's relationship with the institutions and institutions in Nagari Lubuk Basung. The institutional aspect can be seen from the cultivator's relationship with the institutions and institutions in Nagari Lubuk Basung. The feasibility value of the goldfish and tilapia cultivation business in KAD is like the investment value of IDR 461,620,000 (goldfish farming) and IDR 289,940,000 (tilapia fish farming).The largest production was for carp ±38 tons/year from 4 ponds, for tilapia ±54 tons/year from 3 ponds. The largest amount of income is IDR 1,152,000,000 (carp) and IDR 1,188,000,000 (tilapia). NPV 10% IDR 2,996,074,627 (10 Years), BCR 1.54, IRR > 26% business can be developed from this value.